2011
DOI: 10.1128/iai.05338-11
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a Streptococcus mutans Antigen Expressed by a Salmonella Vector Vaccine in Dendritic Cell Activation

Abstract: A Salmonella vector vaccine expressing the saliva-binding region (SBR) of the adhesin AgI/II of Streptococcus mutans has been shown to induce a mixed Th1/Th2 anti-SBR immune response in mice and to require Toll-like receptor 2 (TLR2), TLR4, and MyD88 signaling for the induction of mucosal anti-SBR antibody responses. Since dendritic cells (DC) are critical in innate and adaptive immunity, the present study assessed the role of SBR expression by the vector vaccine in DC activation. Bone marrow-derived DC from w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Although no change in effect was observed for the BMDC surface phenotype induced by the differently grown S. epidermidis cells, bacteria obtained from biofilms with higher proportions of dormant cells induced lower production of TNF-α, IL-12 and IL-6 (). A disparate effect on cytokine production by murine dendritic cells upon stimulation with bacterial preparations that induced expression of CD80 and CD86 to indistinguishable levels was also found elsewhere (Xu et al , 2011). It is noteworthy that bacteria obtained from low dormancy biofilms induced cytokine production by BMDCs to the same extent as bacteria obtained from planktonic cultures.…”
Section: Resultssupporting
confidence: 73%
“…Although no change in effect was observed for the BMDC surface phenotype induced by the differently grown S. epidermidis cells, bacteria obtained from biofilms with higher proportions of dormant cells induced lower production of TNF-α, IL-12 and IL-6 (). A disparate effect on cytokine production by murine dendritic cells upon stimulation with bacterial preparations that induced expression of CD80 and CD86 to indistinguishable levels was also found elsewhere (Xu et al , 2011). It is noteworthy that bacteria obtained from low dormancy biofilms induced cytokine production by BMDCs to the same extent as bacteria obtained from planktonic cultures.…”
Section: Resultssupporting
confidence: 73%
“…They found that the iscl- null mutants of L. major completely abolished their virulence in BALB/c mice, partially due to parasite’s defects in survival under an acid pH condition; however, a low number of mutant parasites could persist in the injection site for several months (Zhang et al, 2009; Xu et al, 2011). In sharp contrast, the iscl- deficient L. amazonensis are fully virulent in BALB/c mice, but are partially attenuated in C57BL/6 mice (K. Zhang, personal communication).…”
Section: Amazonensis Parasites Can Exploit Host’s Lipid Metabolismmentioning
confidence: 99%
“…AgI/II family molecules are considered to mediate bacterial adhesion to mucosal glycoproteins (9 -13) as well as to the extracellular matrix (14 -17) and other bacteria (18 -21). The contribution of P1 to bacterial adherence, colonization, and cariogenicity and its promise in clinical trials make it a therapeutic target and focus of immunization studies (22)(23)(24)(25)(26). In the oral environment within the salivary pellicle on tooth surfaces, S. mutans P1 interacts primarily with the glycoprotein salivary agglutinin complex (SAG) comprising predominantly the scavenger receptor gp340/DMBT1 (11-13, 22, 27-37).…”
mentioning
confidence: 99%